Haus oder Schule? oder Haus und Schule? Zur kulturell-gesellschaftlichen Bedeutung der historischen Textsorte 'Schulprogramm' hinsichtlich der Konstitution, Festigung wie Abgrenzung des Erziehungssystems im 19. Jahrhundert - Markewitz, Friedrich (Textsorten in Sprach-, Kultur- und Sozialgeschichte)

Ironie - Markewitz, Friedrich
Ironie lässt sich als uneigentliches Kommunikationsmittel beschreiben, mit dem etwas anderes zum Ausdruck gebracht wird, als Sprecher*innen oder Schreiber*innen eigentlich meinen. Dies erfordert eine Differenzierung in Gesagtes und Gemeintes. Doch diese Differenzierung ist längst nicht immer eindeutig und so lebt Ironie von einer interpretatorischen Ambivalenz, ob eine Äußerung wörtlich oder ironisch zu verstehen ist. Aufgrund dieser Ambivalenz und ihrer kulturgeschichtlichen Entwicklung erscheint Ironie als ebenso faszinierendes wie komplexes Sprach-Phänomen. Die vorliegende Einführung gibt aus kulturlinguistischer Perspektive Einblicke in die verschiedenen Möglichkeiten der theoretischen Beschreibung, methodischen Erfassung sowie empirischen Analyse von Ironie. Dabei werden einerseits alltagssprachliche Formen ironischen Kommunizierens in den Blick genommen, andererseits Möglichkeiten des interdisziplinären Anschlusses, um Ironie als linguistisches sowie als kulturgeschichtliches Phänomen zugänglich zu machen.

Method development (modelling, simulation, characterisation) in adhesive bonding technology - Beule, Felix; Al Trjman, Mohamad; Teutenberg, Dominik; Meschut, Gerson

Experimentelle und numerische Analyse des Fließverhaltens von hochviskosen Wärmeleitstoffen im Fertigungsprozess - Gilich, Julian; Meschut, Gerson; Gröger, Benjamin; Wiebicke, Felix; Koch, Ilja; Gude, Maik (14. Doktorandenseminar Klebtechnik)

A large deformation gradient theory for glassy polymers by means of micromorphic regularization - Hamdoun, Ayoub; Mahnken, Rolf (Archive of Applied Mechanics)
Abstract Cold forming of polycarbonate films results in the formation of shear bands in the necking zone. The numerical results obtained from standard viscoplastic material models exhibit mesh size dependency, requiring mathematical regularization. For this purpose, we present in this work a large deformation gradient theory for a viscoplastic isotropic material model published before. We extend our model to a micromorphic model by introducing a new micromorphic variable as an additional degree of freedom along with its first gradient. This variable represents a microequivalent plastic strain. The relation between the macroequivalent plastic strain and the micromorphic variable is accomplished by a micromorphic coupling modulus. This coupling forces proximity between the macro- and microvariables, leading to the targeted regularization effect. The micromorphic model is implemented as a three-dimensional initial boundary value problem in an in-house finite element tool. The analysis is performed for both uniaxial and biaxial specimens. The provided numerical examples show the ability of our model to regularize shear bands within the specimens and address the issue of localization.

Digitale Plattformen im industriellen Mittelstand

Uniaxial and biaxial experimental investigation of glassy polymers - Hamdoun, Ayoub; Mahnken, Rolf (Polymer)

Einfluss von Luftfeuchtigkeit auf die Fließfähigkeit von Polymerpulvern für das selektive Lasersintern (Studienarbeit) - Walljasper, Ben

Entwicklung eines Bildanalyseverfahrens zur Erfassung des dynamischen Fließverhaltens von Schüttgütern - Liu, Diyi

Glycemic response to meals with a high glycemic index differs between morning and evening: a randomized cross-over controlled trial among students with early or late chronotype - Stutz, Bianca; Krueger, Bettina; Goletzke, Janina; Jankovic, Nicole; Alexy, Ute; Herder, Christian; Dierkes, Jutta; Berg-Beckhoff, Gabriele; Jakobsmeyer, Rasmus; Reinsberger, Claus; Buyken, Anette (European Journal of Nutrition)
Abstract Purpose Glycemic response to the same meal depends on daytime and alignment of consumption with the inner clock, which has not been examined by individual chronotype yet. This study examined whether the 2-h postprandial and 24-h glycemic response to a meal with high glycemic index (GI) differ when consumed early or late in the day among students with early or late chronotype. Methods From a screening of 327 students aged 18–25 years, those with early (n = 22) or late (n = 23) chronotype participated in a 7-day randomized controlled cross-over intervention study. After a 3-day observational phase, standardized meals were provided on run-in/washout (days 4 and 6) and intervention (days 5 and 7), on which participants received a high GI meal (GI = 72) in the morning (7 a.m.) or in the evening (8 p.m.). All other meals had a medium GI. Continuous glucose monitoring was used to measure 2-h postprandial and 24-h glycemic responses and their variability. Results Among students with early chronotype 2-h postprandial glucose responses to the high GI meal were higher in the evening than in the morning (iAUC: 234 (± 92) vs. 195 (± 91) (mmol/L) × min, p = 0.042). Likewise, mean and lowest 2-h postprandial glucose values were higher when the high GI meal was consumed in the evening (p < 0.001; p = 0.017). 24-h glycemic responses were similar irrespective of meal time. Participants with late chronotype consuming a high GI meal in the morning or evening showed similar 2-h postprandial (iAUC: 211 (± 110) vs. 207 (± 95) (mmol/L) × min, p = 0.9) and 24-h glycemic responses at both daytimes. Conclusions Diurnal differences in response to a high GI meal are confined to those young adults with early chronotype, whilst those with a late chronotype seem vulnerable to both very early and late high GI meals. Registered at clinicaltrials.gov (NCT04298645; 22/01/2020).

Modular 3D roller straightening – A new approach to straightening and forming of spring steel wires (X10CrNi18-8) - Dahms, Frederik Simon; Homberg, Werner (Materials Research Proceedings)
Abstract. Spring steel wires are usually supplied and stored on coils. The manufacturing and coiling processes of these wires induce inhomogeneous plastic deformations that lead to undesirable residual stresses and varying wire curvatures in the semi-finished product. These residual stresses and curvatures defects are causing varying process conditions in the subsequent manufacturing processes, which have a negative impact on the product quality, leading to wastage and thus affecting the economic and ecological efficiency. Especially the curvature deviations must be compensated for the stability of the subsequent processes. This is usually realised with roller straighteners, which are set manually by the machine operators only at the beginning of a process. In this paper, we introduce a new approach with a modular straightening-machine design and a new set-up process. The more isolated deformation behaviour in a module-based straightener overcomes the complexity of interactions between the close-positioned spaced straightening rollers. This is combined with a set-up process that is independent of conventional material testing, modelling the actual and batch-specific behaviour of the wire in the straightening process. The exact knowledge and time-consuming determination of the material properties thus becomes obsolete. The experimental investigations show the influence of defined straightening strategies on the residual stress evolution and the residual forming limit of the spring steel wires (X10CrNi18-8) in the new straightening process.

Alexandra Treder (Universität Paderborn) rezensiert: Döll, Marion & Michalak, Magdalena (2023): Deutsch als Zweitsprache und inklusive Bildung. [Deutsch als Zweitsprache – Positionen, Perspektiven, Potenziale, Bd. 3]. Münster: Waxmann, 142 Seiten. ISBN 978-3-8309-4711-0. - Treder, Alexandra (Forschungsportal für Spracherwerb und Migration (daz-portal))

Mechanically Joined Extrusion Profiles for Battery Trays - Neumann, Stefan; Meschut, Gerson; Otroshi, Mortaza; Kneuper, Florian; Schulze, Andre; Tekkaya, Erman

Experimentelle und modellbasierte Untersuchungen zum Prozessverhalten von teilkristallinen Materialien im Spritzgießsonderverfahren GITBlow - Kröker, Michael

Die Schrift entHeiligen. Praktisch-theologische Überlegungen zum Bibelgebrauch als Transformation des Heiligen - Schroeter-Wittke, Harald (Heilige Schriften in der Kritik. XVII. Europäischer Kongress für Theologie (5.-8. September 2021 in Zürich). VWGTh 68)

Predicting the Bond Quality of Heavy Copper Wire Bonds using a Friction Model Approach - Althoff, Simon
Ultraschall-Drahtbonden ist eine Standardtechnologie im Bereich der Aufbau- und Verbindungstechnik von Leistungshalbleitermodulen. Um Prozessschritte und damit wertvolle Zeit zu sparen, sollen die Kupferdickdrähte für die Leistungshalbleiter auch für die Kontaktierung von eingespritzten Anschlusssteckern im Modulrahmen verwendet werden. Das Kontaktierungsverfahren mit diesen Drähten auf Steckern in dünnwandigen Kunststoffrahmen führt häufig zu unzureichender Bondqualität. In dieser Arbeit wird das Bonden von Anschlusssteckern experimentell und anhand von Simulationen untersucht, um die Prozessstabilität zu steigern. Zunächst wurden Experimente auf Untergründen mit hoher Steifigkeit durchgeführt, um Störgrößen von Untergrundeigenschaften zu verringern. Die gewonnenen Erkenntnisse erlaubten die Entwicklung eines Simulationsmodells für die Vorhersage der Bondqualität. Dieses basiert auf einer flächenaufgelösten Reibarbeitsbestimmung im Fügebereich unter Berücksichtigung des Ultraschallerweichungseffektes und der hierdurch entstehenden hohen Drahtverformung. Experimente an den Anschlusssteckern im Modulrahmen zeigten eine verringerte Relativverschiebung zwischen Draht und Stecker, was zu einer deutlichen Verringerung der Reibarbeit führt. Außerdem wurden verminderte Schwingamplituden des Bondwerkzeugs nachgewiesen. Dies führt zu einer weiteren Reduktion der Reibarbeit. Beide Effekte wurden mithilfe eines Mehrmassenschwingers modelliert. Die gewonnenen Erkenntnisse und die erstellten Simulationsmodelle ermöglichen die Entwicklung von Klemmvorrichtungen, welche die identifizierten Störgrößen gezielt kompensieren und so ein verlässliches Bonden der Anschlussstecker im gleichen Prozessschritt ermöglichen, in dem auch die Leistungshalbleiter kontaktiert werden.
Keywords: heavy copper bonding; wire bonding; quality prediction; friction model; point-contact-element

Modellierung und Optimierung reibungsbasierter Ultraschall-Pulvertransportprozesse - Dunst, Paul
Der Transport feiner Pulver mit in der Regel sehr hohen adhäsiven und kohäsiven Eigenschaften stellt für viele konventionelle Transportsysteme eine große Herausforderung dar. Durch die Anwendung von Ultraschallschwingungen können insbesondere die hohen adhäsiven Kontaktkräfte und damit auch die Reibungseigenschaften manipuliert werden. Ein neu entwickeltes Pulvertransportsystem nutzt Ultraschallschwingungen, um die effektiven Tangentialkräfte im Pulver-Rohrkontakt zu reduzieren. Durch den koordinierten Einsatz von Ultraschallpulsen während einer niederfrequenten harmonischen Axialschwingung des Transportrohres wird ein kontinuierlicher Pulvertransport ermöglicht. Nach einer Einführung in die Grundlagen der Reibung und Reibungsmanipulation von Festkörpern und Pulvern sowie der Charakterisierung von Pulvern wird das Pulvertransportsystem auf Basis der Reibungsmanipulation inklusive der Leistungselektronik und der Ansteuerungshardware vorgestellt. Eine Sensitivitätsanalyse zeigt, dass die Anregungsparameter des Pulvertransportsystems ein großes Optimierungspotential aufweisen. Es wird ein effizientes, modulares Modell des Pulvertransportsystems vorgestellt, welches neben dem eigentlichen Modell des Transportprozesses ein Modell der Rohrschwingung und ein kennlinienbasiertes Modell des Pulver-Rohrkontakts beinhaltet. Mithilfe des Modells des Pulvertransportsystems werden Anregungsparameter hinsichtlich Amplituden und Frequenzen der auftretenden Schwingungen sowie der Schaltzeiten des Ultraschallpulses optimiert.
Keywords: Ultraschall; Pulvertransport; Modellierung; Optimierung; Reibung; Adhäsion; Kohäsion; Reibungsmanipulation

Hardware-in-the-Loop-Simulation von HD-Scheinwerfer-Steuergeräten zur Entwicklung von Lichtfunktionen in virtuellen Nachtfahrten - Rüddenklau, Nico

Entwurf und Analyse modellprädiktiver Regelungsansätze zur Steigerung des Immersionsempfindens in interaktiven Fahrsimulationen - Biemelt, Patrick

Development of a numerical simulation model for self-piercing riveting of additive manufactured AlSi10Mg - Heyser, Per; Petker, Rudolf; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Laser additive manufacturing processes are used for the production of highly complex geometric structures due to their high geometric freedom. Additive manufacturing processes, in particular powder-based selective laser melting, are used to produce metallic additive manufactured components for the automotive and aerospace industries. Different materials are often joined together to realize sustainable lightweight construction. The production of such mixed construction joints is often realized using mechanical joining technology (e.g. self-piercing riveting). However, there is currently very little experience with the mechanical joining of metallic additive manufacturing components. Furthermore, there is insufficient knowledge about the effects that occur during the mechanical joining of additive manufacturing components. In this article, a method is presented to investigate the joinability of additively manufactured components with conventionally manufactured components using a numerical simulation of the self-piercing riveting process. For this purpose, the additive manufacturing materials are characterized experimentally, the simulation model is configured, and the joining process with additive manufacturing materials is represented in the numerical simulation. Furthermore, the influence of the building direction on the mechanical properties is shown using miniature tensile specimens. Besides the configuration of the simulation model, the influence of heat treatment on the self-piercing riveting process is presented.
Keywords: Mechanical Engineering; General Materials Science